An Assessment of some of the Poisonous Plant Species to Animals found in Delta State, Nigeria - Erhenhi, A.H.; Lemy, E.E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This study investigated some poisonous plants to animals in three communities viz; Ebor-Orogun in Ughelli North Local Government Area; Kwale in Ndokwa West Local Government Area and Ozoro in Isoko South Local Government Area, all in Delta State, Nigeria. Dried leaves, roots and tubers of Dennettia tripetala, Cola nitida, Dracaena marginata, Cucumis melo, Terminalia catappa, Persea americana, Manihot esculenta, Telfaira occidentalis and Vernonia amygdalina were grounded to coarse powders and 16g of each powder was weighed into a conical flask. Distilled water (120cm3) was added and the content was shaken and kept for 48hours at room temperature. Filtration of the extract was carried out using whatman No1 filter paper and concentrated using vacuum evaporator. Phytochemical analysis was carried out using standard methods. The results revealed that there were nine (9) indigenous plants with poisonous effects to animals as reported by the community dwellers, among the selected plants and these include: D. tripetala, C. nitida, D. marginata and C. melo, T. catappa, P. americana, M. esculenta (tuber), T. occidentalis (root) and V. amygdalina (root). Qualitative analysis showed the presence of alkaloid, anthocyanines, cardiac glycoside, flavonoid, glycoside, phenol, reducing sugar, saponin, saponin, tannin and terpenoid in low, moderate and high level in the plants. The chemical quantification revealed the presence of tannin (26.90%, 22.95%, 27%) in C. melo, D. tripetala and C. nitida, saponin (13%) in N. laewis, cyanogenic glycoside (3.24mg/l, 1.11mg/l) in M. esculenta and V. amygdalina followed by hydrogen cyanide (0.76mg/l, 0.75mg/l, 6.41mg/l) in P. americana, T. catappa and T. occidentalisas the major cause of poisoning in the plants encountered.There is need for evaluation of the effects of these substances on the organs and systems of animals in order to ascertain the actual site of toxicity of these substances.